Eviction-driven infanticide and sexually selected adoption and infanticide in a neotropical parrot - Beissinger, Steven R; Berg, Karl S (Proceedings of the National Academy of Sciences - PNAS, 2024)
Infanticide and adoption have been attributed to sexual selection, where an individual later reproduces with the parent whose offspring it killed or adopted. While sexually selected infanticide is well known, evidence for sexually selected adoption is anecdotal. We report on both behaviors at 346 nests over 27 y in green-rumped parrotlets ( ) in Venezuela. Parrotlets are monogamous with long-term pair bonds, exhibit a strongly male-biased adult sex ratio, and nest in cavities that are in short supply, creating intense competition for nest sites and mates. Infanticide attacks occurred at 256 nests in two distinct contexts: 1) Attacks were primarily committed by nonbreeding pairs (69%) attempting to evict parents from the cavity. Infanticide attacks per nest were positively correlated with population size and evicting pairs never adopted abandoned offspring. Competition for limited nest sites was a primary cause of eviction-driven infanticide, and 2) attacks occurred less frequently at nests where one mate died (31%), was perpetrated primarily by stepparents of both sexes, and was independent of population size. Thus, within a single species and mating system, infanticide occurred in multiple contexts due to multiple drivers. Nevertheless, 48% of stepparents of both sexes adopted offspring, and another 23% of stepfathers exhibited both infanticide and long-term care. Stepfathers were often young males who subsequently nested with widows, reaching earlier ages of first breeding than competitors and demonstrating sexually selected adoption. Adoption and infanticide conferred similar fitness benefits to stepfathers and appeared to be equivalent strategies driven by limited breeding opportunities, male-biased sex ratios, and long-term monogamy.